1997
DOI: 10.1046/j.1365-2850.1997.00042.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the psychiatric/mental health nursing research literature 1982–1992

Abstract: The purpose of this study was to assess the quality of quantitative psychiatric/mental health nursing research articles published in English between 1982 and 1992, worldwide. Criteria for selection of articles included nurse authorship or co-authorship, use of a quantitative design and pertinence to an aspect of the nursing process with psychiatric/mental health patients. One hundred and ninety-four articles met these criteria. The quality of each article was assessed by two nurse experts using Duffy's Researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…suggest that in recent time bibliometrics has become attractive to research funders and policymakers, as it promises some possible measurement of productivity. Bibliometric analysis has been used in other countries to quantify research and publication output in nursing, for example, Australia , America (Zauszniewski & Suresky 2003), Canada (Yonge et al 1997), Slovenia (Dornik et al 2005), Taiwan (Huang & Chuang 2006) and the UK . Common themes from these analyses were the rapid growth of nursing research and publications in comparison with other professional groups, the overrepresentation of research to do with professional issues as opposed to the care of patients, and concerns on methodology issues, such as sampling and rigour.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…suggest that in recent time bibliometrics has become attractive to research funders and policymakers, as it promises some possible measurement of productivity. Bibliometric analysis has been used in other countries to quantify research and publication output in nursing, for example, Australia , America (Zauszniewski & Suresky 2003), Canada (Yonge et al 1997), Slovenia (Dornik et al 2005), Taiwan (Huang & Chuang 2006) and the UK . Common themes from these analyses were the rapid growth of nursing research and publications in comparison with other professional groups, the overrepresentation of research to do with professional issues as opposed to the care of patients, and concerns on methodology issues, such as sampling and rigour.…”
Section: Methodsmentioning
confidence: 99%
“…2002, Wilkes et al . 2002), America (Zauszniewski & Suresky 2003), Canada (Yonge et al . 1997), Slovenia (Dornik et al .…”
Section: The Studymentioning
confidence: 99%
“…In the data evaluation stage of the integrative review, the Research Appraisal Checklist (RAC) (Duffy 1985) was used to assess the scientific quality of the included studies. The RAC-scale has been used in earlier publications (Brown 1990, Yonge et al 1997, Beeckman et al 2009) and contains 51 assessment criteria, ordered in 10 categories e.g. abstract, problem, data analysis and style.…”
Section: Quality Appraisalmentioning
confidence: 99%
“…As a point of comparison, a brief review of nursing research studies revealed notation of obtained funding rates ranging from 37% (Yonge et al, 1997) to 48% (Molassiotis et al, 2006). While the funding rate for empirical articles within occupational science literature falls within this range, it is at the lower end.…”
Section: Funding and Publication Sourcementioning
confidence: 99%